The Verdict on Advertisements for Near Eastern Antiquities—Dubitante - Shanks, Hershel (The Biblical archaeology review, 1984)
Supreme Court Justices are paid to decide difficult cases. In 1951, however, Justice Felix Frankfurter heard a case he couldn’t decide.a His brethren voted to affirm the decision of the court below. But Justice Frankfurter couldn’t make up his mind. So he took the unusual—perhaps unique—step of filing an opinion neither affirming nor reversing, […]